Peatland-Adaptive Commodity Adoption: Determinants, Income Impact, and Its Relationship with Restoration in Banjar Regency, South Kalimantan\ (Jurnal Sosial Ekonomi Pertanian, 2026)
This study aims to analyze the factors influencing the adoption of peatland-adaptive commodities, their impact on farmers' income, and their relationship with peatland restoration program support in Banjar Regency, South Kalimantan. An analytical observational cross-sectional design was employed with 100 farmer respondents (49 Adapters and 51 non-Adapters) selected through purposive random sampling in Gambut and Aluh-Aluh Districts from April to August 2025. Data were analyzed using Spearman correlation, Mann-Whitney U, Chi-Square, Pearson correlation, and forward stepwise logistic regression. The results indicate that price fluctuation is the only significant factor influencing adoption (OR=1.999; p=0.008). Livestock Adapters had significantly higher income of IDR 30.0 million (113.7%) compared to non-Adapters (p=0.023), while horticultural Adapters showed no significant difference (p=0.614). Adoption status did not correlate with restoration attitudes (r=0.036; p=0.719) or restoration program participation (r=0.029; p=0.776), although a strong positive correlation was found between restoration attitudes and participation (r=0.586; p
Keywords: Adaptive Commodities; Farmer Income; Innovation Adoption; Peatland; Peatland Restoration